2006
DOI: 10.1111/j.1601-0825.2005.01225.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral cancer: experiences and diagnostic abilities elicited by dentists in North‐western Spain

Abstract: Our data from Spain suggest a need for improving the diagnostic ability of GDPs in the visual detection of oral cancer/precancer by strengthening continuing professional education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 63 publications
1
47
2
3
Order By: Relevance
“…38 The high degree of accuracy and high positive and negative predictive values (81.9% and 98.9%, respectively) for clinical diagnosis of PMD and malignant lip lesions in this study reflect clinicians' ability to discern the nature of these cases correctly. The overall accuracy and sensitivity of clinical diagnosis found in this study are greater than reported in previous studies, 20,26 but this difference must be interpreted with caution, given that our sample included only lip lesions. On the other hand, the sensitivity of clinical diagnosis of malignant lesions and disorders of epithelial maturation separately was lower (57% and 52%, respectively).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…38 The high degree of accuracy and high positive and negative predictive values (81.9% and 98.9%, respectively) for clinical diagnosis of PMD and malignant lip lesions in this study reflect clinicians' ability to discern the nature of these cases correctly. The overall accuracy and sensitivity of clinical diagnosis found in this study are greater than reported in previous studies, 20,26 but this difference must be interpreted with caution, given that our sample included only lip lesions. On the other hand, the sensitivity of clinical diagnosis of malignant lesions and disorders of epithelial maturation separately was lower (57% and 52%, respectively).…”
Section: Discussioncontrasting
confidence: 54%
“…23 The rate of concordance between clinical and histopathological diagnoses of oral lesions ranges from 36% to 50%. 24,25,26,27 In contrast, a few studies have reported high degrees of sensitivity and specificity, and high positive predictive value, of clinical oral examination for the detection of malignancies, 28,29,30 indicating that the initial clinical evaluation is reliable for the early detection of malignant and PMD lesions. More importantly, clinicians' decision making following such examination can be supported by knowledge of diagnostic accuracy.…”
Section: Introductionmentioning
confidence: 96%
“…Education actions are needed to increase the awareness of these associations and to encourage individuals to give up habits involved in the pathogenesis of oral cancer. 18 Although the National Oral Health Policy included the diagnosis of oral lesions, with special emphasis on oral cancer, 13 in the scope of practice of primary health care facilities in 2004, and the PMAQ-AB launched in 2011 15 included an indicator of the incidence of mucosal changes, primary health care dentists still have little knowledge of stomatology. For example, most dentists (74.1%) considered themselves incapable of performing biopsies, which are essential for the early diagnosis of oral lesions.…”
Section: Discussionmentioning
confidence: 99%
“…To test knowledge is surely important an important goal, but these questionnaires are incomplete tools for assessing competence at a professional task. On the other hand, the use of clinical cases (images and clinical records) has been widely utilised for evaluating and training screeners for oral cancer and precancer (14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%